2010
DOI: 10.1002/cphc.200900982
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Surfactant Structure in the Behavior of Hydrophobic Ionic Liquids within Aqueous Micellar Solutions

Abstract: The behavior of an ionic liquid (IL) within aqueous micellar solutions is governed by its unique property to act as both an electrolyte and a cosolvent. The influence of the surfactant structure on the properties of aqueous micellar solutions of zwitterionic SB-12, nonionic Brij-35 and TX-100, and anionic sodium dodecyl sulfate (SDS) in the presence of the "hydrophobic" IL 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF(6)]) is assessed along with the possibility of forming oil-in-water microemulsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Such studies have clearly demonstrated the effectiveness of ILs in tuning the key physicochemical properties of these systems because of their impressive solvation ability which facilitates interaction with classical surfactants and have attracted widespread attention due to the multifaceted practical uses of such systems [11][12][13][14][15][16]. Interestingly, most of these studies were involved with a conventional anionic surfactant, sodium dodecylsulphate (SDS) [14,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…Such studies have clearly demonstrated the effectiveness of ILs in tuning the key physicochemical properties of these systems because of their impressive solvation ability which facilitates interaction with classical surfactants and have attracted widespread attention due to the multifaceted practical uses of such systems [11][12][13][14][15][16]. Interestingly, most of these studies were involved with a conventional anionic surfactant, sodium dodecylsulphate (SDS) [14,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…The dc conductivity of bmimPF 6 solution σ m ranges from 0.17 S/m to 0.65 S/m. 32 A first estimation indicates that τ MW ranges from 4.2 to 1.1 ns in the IL/water phase region, which is in the same order as the relaxation time of the low-frequency relaxation. Therefore, this mechanism is possibly responsible for the low-frequency relaxation, but it cannot contribute to the high-frequency relaxation because even the slowest relaxation process involved in the high-frequency relaxation has a relaxation time of the order of 100 ps (see Table I).…”
Section: B Mechanisms Of the Relaxationsmentioning
confidence: 99%
“…It should be pointed out that, when φ w > 0.8 the water phase is saturated with bmimPF 6 (about 2.1 wt. %); therefore the dc conductivity of saturated bmimPF 6 solution (around 0.65 S/m) 32 is taken for σ m (IL/water and B.C. phases) or σ p (water/IL phase).…”
Section: The Low-frequency Relaxationmentioning
confidence: 99%
“…Comprehensive studies on the interactions between mixtures of gemini and conventional single chain surfactants of different charge classes to form mixed micellar aggregates have been reported [31][32][33][34]. In recent decades, studies on the interactions between single chain surfactants and IL have been reported and the results obtained are discussed at length [35][36][37][38][39][40][41][42][43][44][45][46]. Pandey et al [35][36][37][38] reported the dual behavior of IL in aqueous solutions of single chain surfactants.…”
Section: Introductionmentioning
confidence: 99%